2006
DOI: 10.1073/pnas.0506112103
|View full text |Cite
|
Sign up to set email alerts
|

Nonvascular VEGF receptor 3 expression by corneal epithelium maintains avascularity and vision

Abstract: Transparency of the cornea, the window of the eye, is a prerequisite for vision. Angiogenesis into the normally avascular cornea is incompatible with good vision and, therefore, the cornea is one of the few tissues in the human body where avascularity is actively maintained. Here, we provide evidence for a critical mechanism contributing to corneal avascularity. VEGF receptor 3, normally present on lymphatic and proliferating blood vascular endothelium, is strongly constitutively expressed by corneal epitheliu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
183
0
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 233 publications
(188 citation statements)
references
References 27 publications
0
183
0
5
Order By: Relevance
“…These mechanisms include an intact corneal epithelial layer; soluble immunomodulatory factors in the aqueous humor, the blood-ocular barrier; epithelial expression of membrane and soluble vascular endothelial growth factor receptors (VEGFRs) 1,2 ; and the high expression of Fas ligand and thrombospondin-1. [3][4][5][6] Recently, another immunoregulatory molecule, programmed death ligand-1 (PD-L1, also known as CD274 or B7-H1), has been shown to be expressed at high levels by corneal tissue by our laboratory and others.…”
mentioning
confidence: 99%
“…These mechanisms include an intact corneal epithelial layer; soluble immunomodulatory factors in the aqueous humor, the blood-ocular barrier; epithelial expression of membrane and soluble vascular endothelial growth factor receptors (VEGFRs) 1,2 ; and the high expression of Fas ligand and thrombospondin-1. [3][4][5][6] Recently, another immunoregulatory molecule, programmed death ligand-1 (PD-L1, also known as CD274 or B7-H1), has been shown to be expressed at high levels by corneal tissue by our laboratory and others.…”
mentioning
confidence: 99%
“…3). Corneal avascularity, which is a prerequisite for intact vision, is achieved by maintaining of low corneal levels of VEGF expression and strong expression of vascular endothelial growth factor receptor 3 (VEGFR-3) by corneal epithelium [48]. Up-regulation of both VEGF-C and VEGFR-3 has also been demonstrated in inflamed rat corneas [49].…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 99%
“…Upregulation of matrix-derived anti-angiogenic factors such as endostatin (Kato et al, 2003) and restin (Saika et al, 2004), along with increased anti-inflammatory factor IL-1ra may play an important role in LSC and AM transplantation-mediated anti-angiogenic effect. Recently, Cursiefen et al demonstrated a critical mechanism that contributed to corneal avascularity by VEGF receptor 3, which is normally present on lymphatic and proliferating blood vascular endothelium, is strongly constitutively expressed by corneal epithelium and is mechanistically responsible for suppressing inflammatory corneal angiogenesis (Cursiefen et al, 2006). Knowledge gained from using epithelia-matrix interaction to regulate corneal angiogenesis will enable us to optimize the anti-angiogenic effect of the cultivated cells like oral mucosal epithelial cells or mesehchymal stem cells for future ocular surface reconstruction.…”
Section: Combination Techniques With Anti-angiogenic Treatmentsmentioning
confidence: 99%